The Effect of Combination of Hydroxypropylmethylcellulose and Carboxymethylcellulose Sodium Polymers to The Physical Properties of Celery (Apium graveolens L.) Ethanolic Extract Patch - Dian Eka Ermawati; Galuh Kartikasari (Faculty of Pharmacy, Universitas Gadjah Mada, 2020)
Celery herbs (Apium graveolens L.) contain apigenin compounds (flavonoids) that are effective as antihypertensiv. Celery herbs used in the form of decoction and oral preparations have a deficiency that is voluminous and can cause gastric irritation. Patches were chosen because it can prevent gastric irritation and reduce the frequency of drug administration because the drug is delivered over the skin with a long duration. This study aimed to know the effect of variations in the ratio of the concentrations of hydroxypropyl methylcellulose (HPMC) and carboxymethylcellulose sodium (CMC sodium) polymers to the physical properties of celery herbs ethanol extract patch.This study was conducted with maceration of celery herbs using 96% ethanol and then dispersed in patch made with variations in the concentrations ratio of HPMC and CMC sodium polymers of 3:1, 1:1, and 1:3. Patches were tested for physical properties including organoleptic, pH, thickness, weight, folding endurance, and moisture content. Statistical analysis of test data used One Way ANOVA and Paired Samples T Test.The results of statistical analysis showed that the increase concentrations ratio of CMC sodium polymer in the combination of HPMC and CMC sodium polymers could increase the thickness, weight, and moisture content of celery herbs ethanol extract patch. The best patch was formula 2 with the same concentration ratio of HPMC and CMC sodium polymers because it showed the best results with a pH 6,12-6,29, thickness 1,37-1,53 mm, weighting 2,24-2,52 gram, folding endurance more than 300 times, and the moisture content was quite stable.